Hubungan Kebersihan Rongga Mulut dan Status Gingiva dengan Usia Kehamilan pada Ibu Hamil di Wilayah Kerja Puskesmas Sumbersari Kabupaten Jember - Nadiah Pujiati; Kiswaluyo Kiswaluyo; Masriani Novita (Pustaka Kesehatan, 2020)
Pregnancy causes the hormonal change which will improve the oral health of pregnant women. The hormonal change causes the gingiva to become more sensitive to toxins or irritants which causes inflammation of the gingiva. The Increasing gestational age gives the risk of pregnancy for periodontal tissue damage. This study aims to find out the correlation of oral hygiene and gingival status with gestational age in 97pregnant women in the working area of ​​Sumbersari Health Center Jember Regency. The study was observational analytic using cross sectional study. The oral hygiene status of pregnant women was measured using the Oral Hygiene Index Simplified (OHI-S) and the gingival status measurement using the Gingival Index (GI). The results showed that 73,2% oral hygiene status of pregnant women is moderate. All of the pregnant women in this study had gingivitis and most were moderate gingivitis. There was no correlation between oral hygiene with gestational age, but there was a correlation between gingival status and gestational age in pregnant women. The periodontal care should be obtained to prevent the gingival disease during pregnancy.